Prevalence and factors associated with obesity among the oldest old. (July 2020) - Hajek, André; Brettschneider, Christian; van der Leeden, Carolin; Lühmann, Dagmar; Oey, Anke; Wiese, Birgitt; Weyerer, Siegfried; Werle, Jochen; Fuchs, Angela; Pentzek, Michael; Röhr, Susanne; Löbner, Margrit; et al.
Highlights: Longitudinal data were taken from a multicenter prospective cohort-study. Nearly half of the individuals in very late life had excess weight. Probability of obesity decreased with age and less chronic conditions. It was not associated with other factors, e.g. social isolation or health-related. Excess weight remains a major challenge, even in very old age. Abstract: Purpose: To determine the prevalence of overweight and obesity, and to identify factors associated with obesity, among the oldest old. Methods: For this study, data from follow-up (FU) wave 7 and FU wave 8 of the "Study on Needs, Health Service Use, Costs and Health-Related Quality of Life in a Large Sample of Oldest-Old Primary Care Patients (85+)" (AgeQualiDe) were used. At FU wave 7, the mean age was 88.9 years (SD: 2.9; 85–100 years). Body-mass-index (BMI) categories were defined according to the World Health Organization (WHO) thresholds: underweight (BMI < 18.5 kg/m²), normal weight (18.5 kg/m² ≤ BMI < 25 kg/m²), overweight (25 kg/m² ≤ BMI < 30 kg/m²), and obesity (BMI ≥ 30 kg/m²). Longitudinal regression analysis was used to determine factors associated with obesity. Results: At FU wave 7, 3.0 % were underweight, 48.9 % were normal weight, 37.9 % were overweight, and 10.2 % were obese. Regressions showed that the probability of obesity decreased with age (OR: 0.77 [95 % CI: .593–.999]) and less chronic conditions (OR: 1.32 [95 % CI: 1.11–1.57]). The probability of obesity was not associated with sex, educational level, marital status, social isolation, visual impairment, hearing impairment, depression, and dementia. Conclusion: Nearly half of the individuals in very late life had excess weight. Thus, excess weight remains a major challenge, even in very old age. Given the demographic ageing in upcoming decades, this is an issue which we should be aware of.